2013
DOI: 10.1177/0730888413481481
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity, Strikes, and Scabs

Abstract: This article studies how participation norms affect workers’ willingness to strike. A factor analysis on the responses of 468 Dutch union members about appropriate behavior during a strike produces two factors. The first factor reflects a “solidarity norm” favoring group solidarity; the second factor reflects a norm about the treatment of defecting colleagues, which we call the “free-rider-punishment” norm. Using OLS regression, we show that adherence to these norms significantly affects union members’ willing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Moreover, members of the general public endorsing negative stereotypes of activists (e.g., perceive them as militant or eccentric) are less likely to adopt the behaviors they promote [24]. At the same time, activists may judge harshly and/or disidentify from their broader ingroup, if they perceive them as lacking commitment to the group cause [25,26], or failing to show solidarity [27,7]. This suggests that activists may perceive non-activists as too selfish (i.e., focusing too much on their individual interests, as opposed to group interests), whereas non-activists may see activists as complainers.…”
Section: Mutual Perceptions and Communication Of Motivations For Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, members of the general public endorsing negative stereotypes of activists (e.g., perceive them as militant or eccentric) are less likely to adopt the behaviors they promote [24]. At the same time, activists may judge harshly and/or disidentify from their broader ingroup, if they perceive them as lacking commitment to the group cause [25,26], or failing to show solidarity [27,7]. This suggests that activists may perceive non-activists as too selfish (i.e., focusing too much on their individual interests, as opposed to group interests), whereas non-activists may see activists as complainers.…”
Section: Mutual Perceptions and Communication Of Motivations For Actionmentioning
confidence: 99%
“…Communicating shared identities signals inclusion, and can help activists define the non-activists as part of their group [21,4,1], which in turn should make them more popular among non-activists. Finally, prior literature on the negative relations between strikers and strike-breakers [27,7], suggests that activists may be more likely to glorify their group and conversely disparage those who fail to act. Thus, we expect activists to perceive greater differences between themselves and the non-activists, by evaluating their own group more positively and the non-activists more negatively, whereas we expect non-activists to feel equally positive about both groups (Hypothesis 5).…”
Section: Mutual Perceptions and Communication Of Motivations For Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such tensions are not necessarily entirely negative. Both Akkerman, Born & Torenvlied (2013) and Mohrman Tenkasi and Mohrman (2003) show that social networks are important as both influencers and outputs of organizational change processes, whether in moderating participation in collective action or whether members will conform to the intended designs or will pursue more creative and more effective actions (Mohrman Tenkasi & Mohrman, 2003, p. 321) through leveraging resources connected to external networks. Similarly, the trust underpinned by embedded social networks allows change agents to have an impact within organizations; for example, Biniari (2012) found that intra-organizational envy of corporate entrepreneurs is lessened in contexts of high social embeddedness, which means they are more likely to act.…”
Section: Embedding In Internal Intra-organizational Social Networkmentioning
confidence: 99%
“…The formation of an array of ties leads to the fourth aspect, in which the individual's behaviors and decisions are shaped by the these relationship (Chajewski, 2007;Kilduff & Brass, 2010;Roos, 2018) while, at the same time, these behaviors shape the networks within which they are embedded (Halbesleben & Wheeler, 2008;Tasselli, 2015). The influences on the individual received in this way affect the possible course (s) of action that they may consider to be appropriate (Akkerman, Born & Torenvlied, 2013;Sydow, Lindkvist & DeFillippi, 2004, p. 1479. Thus, embeddedness, overall, describes the more-or-less durable and situated nature of the relationships, which constitute social networks.…”
Section: Introductionmentioning
confidence: 99%